Increasing the Capacity of Micro, Small and Medium Enterprises Actors Through the Development Program in North Kolaka Regency - Septiana, Anis Ribcalia; Ashari, Ashari; Mardiana, Mardiana (Universitas Negeri Makassar, 2023)
The high poverty rate and decreasing number of MSMEs in the 2017-2022 period in North Kolaka triggered coaching activities to encourage increased MSME capabilities by the North Kolaka government. The main overview of this research is to examine increasing the capabilities of MSMEs through a development program in North Kolaka which involves various sectors of the Regional Government, Central Government, BUMN/BUMD, and the community. Various findings from interviews, observations and documentation studies were reviewed and analyzed using a qualitative descriptive approach with an interactive model. This research shows an increase in the capabilities of MSMEs in North Kolaka through a coaching program which is realized in several activities in the form of stimulus assistance, business equipment assistance, entrepreneurship assistance, education and digital innovation-based training. This program significantly increases the capabilities of MSME players, both in terms of finance, knowledge, skills and innovation. Increasing MSME capabilities helps create better business management, in the aspects of financial stability, brand creation, packaging, product diversification and digital marketing, and innovation capabilities by utilizing RBA features to prepare business plans based on the OSS RBA application. Apart from that, this activity involving MSMEs opens up space for communication, discussion and interaction between MSME actors, the government and the private sector which can improve the social capabilities of MSME actors in North Kolaka, especially in establishing cooperation and forming mutual benefits. business network. Increasing the capabilities of MSMEs in the Region will have a significant impact on sustainable local economic growth